Love and the Quest for Identity in the Fiction of Henry James. - Sicker, Philip (Princeton Legacy Library, 2017)
Contrary to the majority of Henry James's critics who either have ignored the central importance of love in his work or have mislabeled it as Platonic," "infantile," and "asexual," Philip Sicker shows that romantic love played a substantial role in James's fiction. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905